2019
DOI: 10.1007/s10570-019-02348-6
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing effect of poly(furfuryl alcohol) in cellulose-based porous materials

Abstract: The mechanical reinforcement of porous materials made of microfibrillated cellulose by in situ polymerisation of furfuryl alcohol prior to freezedrying from aqueous slurry was studied. Besides a slight improvement in the modulus of elasticity measured in compression testing, no beneficial effects of furfuryl alcohol addition on porous materials produced from microfibrillated cellulose derived from bleached softwood pulp were observed. By contrast, when microfibrillated cellulose containing substantial amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Based on these results and since most of the modifications took place via electrophilic aromatic substitution, lignin could be the main wood component modified during treatments with FA and tannins, supporting the statement of a strong affinity of FA towards non-cellulosic cell wall constituents during polymerization [37,57,58]. Even if it remains difficult to certify SE Ar between tannins, lignin and furfuryl alcohol based on the FTIR analysis performed in this study, additional studies indicate the possibility of such reactions [59,60].…”
Section: Ftir Analysissupporting
confidence: 76%
“…Based on these results and since most of the modifications took place via electrophilic aromatic substitution, lignin could be the main wood component modified during treatments with FA and tannins, supporting the statement of a strong affinity of FA towards non-cellulosic cell wall constituents during polymerization [37,57,58]. Even if it remains difficult to certify SE Ar between tannins, lignin and furfuryl alcohol based on the FTIR analysis performed in this study, additional studies indicate the possibility of such reactions [59,60].…”
Section: Ftir Analysissupporting
confidence: 76%
“…As shown in Figure , the experimental results demonstrate that the coated paper has slightly higher tensile strength than uncoated papers, indicating a slight enhancement of its mechanical strength. This may be explained by the fact that the PKO and FA coating materials have penetrated the porous cellulose structures of the paper and the cross-linking between FA and cellulose can serve as a reinforcement of the paper in addition to a barrier for the water vapor …”
Section: Resultsmentioning
confidence: 99%
“…This may be explained by the fact that the PKO and FA coating materials have penetrated the porous cellulose structures of the paper and the cross-linking between FA and cellulose can serve as a reinforcement of the paper in addition to a barrier for the water vapor. 50…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The thermograms (TGA) and derivatives of thermograms (DTA) are gathered in Figure 3b. The DTA curves showed that the main peak around 415 • C for PFA was attributed to the degradation of methylene and the furan ring in the PFA chain; the peak at 190 • C was owing to the volatiles that evolved during further condensation polymerization of the PFA resin [26]. MWL lost a little weight before 200 • C, mainly water molecules and some small molecule impurities in the sample, and its decomposition temperature range was mainly between 200 and 500 • C. The weight loss was faster at 302 and 369 • C, and the final carbon residue was 31%.…”
Section: The Polymerization Mechanism Of Pfa and Mwlmentioning
confidence: 99%